Transcutaneous Electrical Nerve Stimulation Improves Walking Performance in Patients With Intermittent Claudication. Issue 4 (July 2016) - Seenan, Chris; McSwiggan, Steve; Roche, Patricia A.; Tan, Chee-Wee; Mercer, Tom; Belch, Jill J. F.
Abstract : The purpose of this study was to investigate the effects of 2 types of transcutaneous electrical nerve stimulation (TENS) on walking distance and measures of pain in patients with peripheral arterial disease (PAD) and intermittent claudication (IC). In a phase 2a study, 40 participants with PAD and IC completed a graded treadmill test on 2 separate testing occasions. Active TENS was applied to the lower limb on the first occasion; and placebo TENS, on the second. The participants were divided into 2 experimental groups. One group received high-frequency TENS; and the other, low-frequency TENS. Measures taken were initial claudication distance, functional claudication distance, and absolute claudication distance. The McGill Pain Questionnaire (MPQ) vocabulary was completed at the end of the intervention, and the MPQ–Pain Rating Index score was calculated. Four participants were excluded from the final analysis because of noncompletion of the experimental procedure. Median walking distance increased with high-frequency TENS for all measures ( P < .05, Wilcoxon signed rank test, all measures). Only absolute claudication distance increased significantly with low-frequency TENS compared with placebo (median, 179–228; W s = 39; z = 2.025; P = .043; r = 0.48). No difference was observed between reported median MPQ–Pain Rating Index scores: 21.5 with placebo TENS and 21.5 with active TENS ( P = .41). Transcutaneous electrical nerve stimulation applied to the lower limb of the patients with PAD and IC was associated with increased walking distance on a treadmill but not with any reduction in pain. Transcutaneous electrical nerve stimulation may be a useful adjunctive intervention to help increase walking performance in patients with IC.